Model Pembelajaran Online di Kelas Tingkat Sekolah Dasar - Dyieka Variedz Zuhriyyah; Marlina Marlina (Diniyah: Jurnal Pendidikan Dasar, 2022)
This study aims to describe the portrait of online learning at SD Negeri 15 Lalembuu, explain the obstacles in its implementation, and describe students' learning motivation in following this learning model. Data collection methods consist of interviews, observation, and documentation, which are then analyzed through data reduction, data presentation, and conclusion. The study shows that online learning at SD Negeri 15 Lalembuu, Konawe Selatan District, uses the WhatsApp application; the teacher creates class groups consisting of teachers, students, and student's parents. Assignments are sent via the WhatsApp group. However, some students did not have cell phones and did not understand the teacher's presentation while studying. Student learning motivation in online learning is divided into motivation that arises from within the student himself and motivation that arises from outside the student's self, namely the family environment, school environment, and community environment.Keywords: Student motivation for learning, online learning, and online learning limitations